The effect of transcranial magnetic stimulation on the concentration of BDNF, cortisol, thyroid-stimulating hormone and thyroxine in the serum of patients with multiple sclerosis - Malakhov, Володимир; Haponov, Петро (Psychosomatic Medicine and General Practice, 2021)
Design, contingent, and research methods. The study was conducted based on the Department of Autoimmune and Degenerative Diseases of the Nervous System, the Center for Multiple Sclerosis of the Institute of Neurology, Psychiatry, and Addiction of the National Academy of Medical Sciences of Ukraine. The results were obtained by examining 110 patients with multiple sclerosis (73 women and 37 men). The diagnosis was made according to the criteria of McDonald et al., 2017. All patients were divided into an intervention group who received a course of pTMS and a comparison group without the use of non-invasive neuromodulation. For noninvasive neuromodulation in the process of treatment and rehabilitation, rTMS was used. The course of treatment was performed on a MagVenture, MagPro X100, and an 8-shaped inductor (coil). Serum levels of cortisol, thyroid-stimulating hormone (TSH), total thyroxine (T4), and BDNF were determined. Results. The use of TMS did not significantly affect the serum cortisol content of patients with progressive types of MS but had a positive effect on GGAS in patients with remitting type. TMS increased the concentration of neurotrophin BDNF in the group of patients with RT MS, and less pronounced, but also significantly - in the group of VPT. TMS led to an increase in TSH levels in the group of patients with RT MS but did not affect the concentration of total thyroxine in the serum. The most sensitive to the effects of TMS is the remitting type of disease. Conclusion. Neurotrophins and hormones play an important role in the processes of remyelination and neuroplasticity. The use of selected parameters of rTMS has a positive effect on the hypothalamic-pituitary system of regulation of glucocorticoid and thyroid hormones, as well as on neurotrophic processes in the CNS in the development of multiple sclerosis. TMS opens new prospects for non-invasive neuromodulation in patients with MS.